Life Quality and Related Factors in Patients Receiving Atrial Fibrillation Ablation - Emine DEMİR; Ayşe DEMİRAY (Journal of Clinical Medical Research, 2026)
Objective: The aim of this study was to evaluate the quality of life and its correlating characteristics in patients who underwent Atrial Fibrillation (AF) ablation. Method: This descriptive study encompassed 72 patients aged 18 years and older who had undergone atrial fibrillation ablation at least three months prior and were subsequently monitored at the Department of Cardiology of a university hospital, either as outpatients attending regular follow-up visits or as inpatients for various reasonsData were collected using a structured questionnaire designed to assess participants’ sociodemographic characteristics and health-related behaviors, as well as the Atrial Fibrillation Effect on Quality of Life Questionnaire (AFEQT). For quantitative variables, data are presented as mean ± standard deviation and median (range). For categorical variables, they were shown as frequency and %. Results: The participants’ average age was 53.7 ± 10.5 years and the average time after AF diagnosis was 44.3 ± 47.1 months. Of the people who took part, 69.4% went for outpatient follow-up and 51.4% were overweight. Palpitations (93.1%), fatigue (52.8%), exhaustion (45.8%) and dyspnea (38.9%) were the AF-related symptoms that people experienced the most. 51.4% of the people who participated said their overall health was “good.” 36.1% said their health had not changed during the previous year and 8.3% said it had become worse. The average scores for the AFEQT subdomains were symptoms 72.6 ± 27.3, daily activities 58 ± 32.9, treatment concern 73.1 ± 27.3 and treatment satisfaction 65.7 ± 25. The total AFEQT score was 66.2 ± 26.2, which means that the quality of life didn’t get worse. Conclusion: It is advisable to do regular long-term monitoring of individuals having ablation to evaluate their quality of life with validated scales. The findings should inform personalized care and educational planning, the formulation of clinical recommendations and the establishment of effective care procedures.